TINJAUAN PROSEDUR BELI JUAL REKSA DANA PADA PT. TRIMEGAH SEKURITAS Tbk - Coni Ayu Carisca (2023)
Investments in mutual funds are managed by investment managers, investment managers provide information and assist investors in investing in mutual funds as needed. In investing in mutual funds, there is a mutual fund buying and selling process which is contained in the specific procedures of each company. In the process of buying and selling transactions at PT. Trimegah Sekuritas has similarities but there are also differences, so that each company has its own process of buying and selling mutual funds. data management using descriptive analysis method with direct observation and conducting interviews with company employees. Purchases and sales of mutual funds must be accompanied by supporting documents. If the document is incomplete, the transaction process cannot be continued. There are several procedures for buying and selling mutual funds from PT. Trimegah Sekuritas Tbk, namely starting from customer service serving customers who will be directed to sales of equity who will later provide forms and guide customers to fill out forms which will then be submitted to the account officer who will input transactions signed by the head of the branch and operational which will first Check mutual fund buying and selling transactions.